Development of an Innovative 3D Printed Rigid Bronchoscopy Training Model. (December 2016) - AL-Ramahi, Jehad; Luo, Huiping; Fang, Rui; Chou, Adriana; Jiang, Jack; Kille, Tony
Objectives: The objective of this study was to create a 3D printed airway model simulating the size and mechanical properties of various age groups for foreign body removal training. Methods: Three-dimensional printing technology was used to print the anatomically correct airway from rubber-like translucent material, simulating the mechanical properties of human airway tissue. The model's effectiveness in trainee education was evaluated by otolaryngology residents with varying levels of experience. As part of an Airway Emergencies course, a rigid bronchoscopy procedure was performed on the 3D printed model as well as a porcine model. The participants completed surveys comparing the validity of the 2 models and the effectiveness of the overall training experience. Results: The 3D printed model, which is accurate in terms of anatomy and mechanical properties, was found to be comparable to a porcine model in regards to participant satisfaction as well as face validity. Conclusions: The 3D printed airway model is able to be accurately scaled to various sizes and simulate the mechanical properties of the desired age group. The 3D printed model provides an excellent alternative to animal models in terms of practicality, logistics of use, and anatomical accuracy.